Targeting glycolytic reprogramming by tsRNA-0032 for treating pathological lymphangiogenesis - Fan Ye; Ziran Zhang; Lianjun Shi; Shuting Lu; Xiumiao Li; Wan Mu; Qin Jiang; Biao Yan (Cell Death and Disease)
Abstract Lymphangiogenesis is vital for tissue fluid homeostasis, immune function, and lipid absorption. Abnormal lymphangiogenesis has been implicated in several diseases such as cancers, inflammatory, and autoimmune diseases. In this study, we elucidate the role of tsRNA-0032 in lymphangiogenesis and its molecular mechanism. tsRNA-0032 expression is significantly decreased in corneal suture model and human lymphatic endothelial cell (HLEC) model under inflammatory condition. Overexpression of tsRNA-0032 exerts anti-lymphangiogenic effects by inhibiting HLEC proliferation, migration, and tube formation. Moreover, overexpression of tsRNA-0032 inhibits suture-induced corneal lymphangiogenesis. tsRNA-0032 is mainly located in the cytoplasm and interacts with Ago2 protein. Overexpression of tsRNA-0032 reduces ATP production and decreases pyruvate and lactate levels by targeting PKM2, a key enzyme in glycolysis. This regulation of glycolysis alters cellular energy and metabolic balance in HLECs, contributing to anti-lymphangiogenic effects. Clinical data reveals that tsRNA-0032 levels are significantly reduced in corneal tissues of transplant recipients compared to donors, while PKM2 expression is elevated, highlighting the clinical relevance of tsRNA-0032/PKM2 axis in corneal lymphangiogenesis. This study offers new insights into the regulation of lymphangiogenesis and presents potential therapeutic targets for lymphangiogenesis-related diseases.